Views of Instructors and Students Regarding Online Measurement and Evaluation Applications - Gonca Usta; Yurdagül Günal; Müge Uluman (Humaniora, 2016)
The purpose of this article was to describe online measurement applications in Turkey by using opinions of instructors as practitioners and students about online measurement. The study group of this qualitative research consisted of 8 instructors offering courses in distance education and 46 students of distance education from Karadeniz Technical University and the University of Cumhuriyet. Answers of lecturers and students were often found to be in parallel. This study finds out that one outstanding difference between participants’ answers that students found online measurement practices reliable whereas instructors disagreed. Students’ opinions about online measuring applications seem more positive than instructors. Our recommendations include taking measures to solve the problems of internet connection, utilizing different types of materials besides multiple-choice items, and preparing of items considering item writing rules regardless of the type of items.